Application of infraorbital rim augmentation with pocket fat filling to correct tear trough deformity - Liu, Yukun; Wang, Yi; Cai, Changqi; Wu, Xiuying; Wang, Haiping (Frontiers in Surgery, 2023)
Background: Tear through deformity is one of the most common complaints in clinical settings. The correction of this groove is challenging in facial rejuvenation. The lower eyelid blepharoplasty varies with different situations. A novel approach of using orbital fat in lower eyelid to increase the volume of infraorbital rim with granule fat injection has been applied in our institution for more than five years. Objectives: This article aims to describe the detailed steps of our technique and verified its effectiveness by cadaveric head dissection after surgical simulation. Methods: In this study, 172 patients underwent lower eyelid orbital rim augmentation with fat filling in the sub-periosteum pocket. According to the volume of orbital fat, 152 patients underwent lower eyelid orbital rim augmentation with orbital fat filling only, 12 had it combined with autologous granule fat from inner thig, and 8 had it with autologous granule fat from inner thig only. Results: Patients were satisfied with the cosmetic results. Excessive protruding fat was released, and the tear trough groove was flattened by using autologous orbital fat transplantation. The lower eyelid sulcus deformities were well corrected. To further illustrate the anatomical structure of lower eyelid area and injection layers, 6 cadaveric head were used for surgical simulation and demonstrated the effectiveness of our technique. Conclusions: This study indicated that infraorbital rim could be increased by transplanting orbital fat to the pocket which was dissected under periosteum, and the procedure has been verified reliable and effective. Evidence Based Medicine (EBM) level: Level II